THE INFLUENCE OF SERVICE QUALITY AND DISCOUNTS ON CUSTOMER SATISFACTION ON GRAB USERS IN MEDAN CITY - Ramayanti Tinambunan, Mey; Syafrizal Helmi Situmorang; Fadli (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
This study, entitled "The Influence of Service Quality and Discounts on Customer Satisfaction on Grab Users in Medan City" aims to examine how Service Quality and Discounts affect Customer Satisfaction. This study uses a descriptive approach, with data analyzed using multiple regression analysis through SPSS. The population consists of 60 respondents and the sampling method used is judgmental purposive sampling. The results of the multiple regression analysis reveal that the Service Quality Variable (X1) has an influence on Customer Satisfaction (Y) on Grab users with a contribution of 0.208 or 20.8%. While the Discount Variable (X2) has an influence on Customer Satisfaction (Y) on Grab users with a contribution of 0.202 or 20.2%. In addition, the coefficient of determination (R2) shows a value of 0.080 or 8% which means that Service Quality and Discount collectively explain 8% of the variance in Job Satisfaction. The remaining 92% is associated with other variables not included in the study